2007
DOI: 10.1017/s0016756807003585
|View full text |Cite
|
Sign up to set email alerts
|

Terminal Cambrian and lowest Ordovician succession of Mexican West Gondwana: biotas and sequence stratigraphy of the Tiñu Formation

Abstract: The Tiñu Formation of Oaxaca State is the only fossiliferous lower Palaeozoic unit between the Laurentian platform in northwest Mexico and Gondwanan successions in Andean South America. The Tiñu traditionally has been referred to the Lower Ordovician (Tremadoc) and regarded as having a provincially mixed fauna with Laurentian, Avalonian, and Gondwanan elements. Bio-and lithostratigraphic re-evaluation demonstrates that the Tiñu is a Gondwanan, passive margin succession. It includes a lower, thin (to 16 m), con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
98
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(100 citation statements)
references
References 58 publications
(123 reference statements)
1
98
0
1
Order By: Relevance
“…Only three such occurrences of orthoceroids are known, and one of these is ambiguous. Slemmestadoceras attavus (Brøgger, 1882) occurs with an as yet undescribed Ellesmeroceras Foerste, 1921 in the middle Tremadocian Bjørksholmen Formation in Norway (Kraeger 2008), and the middle Tremadocian collection from the Rio Salinas Member, Tiµu Formation of Oaxaca State, Mexico, which is dominated by Rioceras and as yet undescribed eothinoceratids (Flower 1968;Landing et al 2007). Wilson (1954) (Thoral, 1935), Bactroceras mourguesi (Thoral, 1935), and Rioceras estivali (Thoral, 1935) (Fortey & Owens 1987).…”
Section: Synopsis -Faunal Composition and Depositional Settingmentioning
confidence: 99%
“…Only three such occurrences of orthoceroids are known, and one of these is ambiguous. Slemmestadoceras attavus (Brøgger, 1882) occurs with an as yet undescribed Ellesmeroceras Foerste, 1921 in the middle Tremadocian Bjørksholmen Formation in Norway (Kraeger 2008), and the middle Tremadocian collection from the Rio Salinas Member, Tiµu Formation of Oaxaca State, Mexico, which is dominated by Rioceras and as yet undescribed eothinoceratids (Flower 1968;Landing et al 2007). Wilson (1954) (Thoral, 1935), Bactroceras mourguesi (Thoral, 1935), and Rioceras estivali (Thoral, 1935) (Fortey & Owens 1987).…”
Section: Synopsis -Faunal Composition and Depositional Settingmentioning
confidence: 99%
“…Landing et al (1978) showed that Cordylodus proavus appears in the Westergaardia Subzone of the middle Acerocare Zone of Avalonian New Brunswick, and this puts an upper bracket on the correlation of the Eoconodontus Zone in the Avalonian and Baltic trilobite successions. The underlying upper Peltura Zones yield Proconodontus serratus¸a chararacteristic form of the Eoconodontus Zone, along with Cordylodus andresi in the Peltura scarabaeoides Zone of Sweden (Szaniawski & Bengtson 1998).…”
Section: Global Correlation Of the Eoconodontus Notchpeakensis Zonementioning
confidence: 99%
“…The lowest specimens of Eoconodontus notchpeakensis occur in platform and upper slope facies of the lower Tiñu Formation in Mexican West Gondwana above the Cordylodus andresi FAD (Landing et al 2007a). Although definition of a biostratigraphically significant E. notchpeakensis FAD can be readily done in the lower Tiñu Formation, the FAD is from a part of the section with provincial (Gondwanan) species of geographically widespread trilobite genera.…”
Section: Global Correlation Of the Eoconodontus Notchpeakensis Zonementioning
confidence: 99%
“…The earliest sedimentary Paleozoic unit is the Tiñú Formation, composed of limestone and shale strata. This unit is divided in a Lower Member of limestone with abundant trilobites, linguliform brachiopods and other invertebrates from the Furongian (late Cambrian) (Robison & Pantoja-Alor, 1968;Landing et al, 2007;Streng et al, 2011), and an Upper Member of shale that records graptolites from the Lower Ordovician (Tremadocian) (Pantoja-Alor, 1970;Sour-Tovar & Buitrón-Sánchez, 1987;Sour-Tovar, 1990).…”
Section: Geological Settingmentioning
confidence: 99%